Объяснение:
Упростим числитель:
1-cos(2a)+sin(2a)=sin²a+cos²a-cos²a+sin²a+2*sina*cosa=
=2*sin²a+2*sina*cosa=2sina*(sina+cosa).
Упростим знаменатель:
1+cos(2a)+sin(2a)=sin²a+cos²a+cos²a-sin²a+2*sina*cosa=
=2*cos²a+2*sina*cosa=2*cosa*(cosa+sina)=2*cosa*(sina+cosa). ⇒
2sina*(sina+cosa)/2*cosa*(sina+cosa)=sina/cosa=tga.
Объяснение:
Упростим числитель:
1-cos(2a)+sin(2a)=sin²a+cos²a-cos²a+sin²a+2*sina*cosa=
=2*sin²a+2*sina*cosa=2sina*(sina+cosa).
Упростим знаменатель:
1+cos(2a)+sin(2a)=sin²a+cos²a+cos²a-sin²a+2*sina*cosa=
=2*cos²a+2*sina*cosa=2*cosa*(cosa+sina)=2*cosa*(sina+cosa). ⇒
2sina*(sina+cosa)/2*cosa*(sina+cosa)=sina/cosa=tga.